Efficacy, safety, and pharmacokinetics of isoniazid affected by NAT2 polymorphisms in patients with tuberculosis: A systematic review - Thanakorn Surarak; Supatat Chumnumwat; Wichit Nosoongnoen; Pramote Tragulpiankit (Wiley, 2024)
Abstract N‐acetyltransferase 2 (NAT2) genetic polymorphisms might alter isoniazid metabolism leading to toxicity. We reviewed the impact of NAT2 genotype status on the pharmacokinetics, efficacy, and safety of isoniazid, a treatment for tuberculosis (TB). A systematic search for research articles published in Scopus, PubMed, and Embase until August 31, 2023, was conducted without filters or limits on the following search terms and Boolean operators: "isoniazid" AND "NAT2." Studies were selected if NAT2 phenotypes with pharmacokinetics or efficacy or safety of isoniazid in patients with TB were reported. Patient characteristics, NAT2 status, isoniazid pharmacokinetic parameters, early treatment failure, and the prevalence of drug‐induced liver injury were extracted. If the data were given as a median, these values were standardized to the mean. Forty‐one pharmacokinetics and 53 safety studies were included, but only one efficacy study was identified. The average maximum concentrations of isoniazid were expressed as supratherapeutic concentrations in adults (7.16 ± 4.85 μg/mL) and children (6.43 ± 3.87 μg/mL) in slow acetylators. The mean prevalence of drug‐induced liver injury was 36.23 ± 19.84 in slow acetylators, which was significantly different from the intermediate (19.49 ± 18.20) and rapid (20.47 ± 20.68) acetylators. Subgroup analysis by continent showed that the highest mean drug‐induced liver injury prevalence was in Asian slow acetylators (42.83 ± 27.61). The incidence of early treatment failure was decreased by genotype‐guided isoniazid dosing in one study. Traditional weight‐based dosing of isoniazid in most children and adults yielded therapeutic isoniazid levels (except for slow acetylators). Drug‐induced liver injury was more commonly observed in slow acetylators. Genotype‐guided dosing may prevent early treatment failure.